The effect of gamification through the learning management system (Blackboard) on stimulating achievement motivation to write a scientific research plan - Alyobi, Reem Abdullah; Alfarani, Leena Ahmad (Journal of Educational and Psychological Sciences, 2022)
The current research aimed at studying the impact of gamification of the scientific research plan on the achievement motivation of female students of educational technology and the extent of their satisfaction. Sequential quantitative – qualitative mixed method approach were used, Quasi-experimental Methodology (One-group post-test design) and Descriptive Methodology (one shot survey and unstructured interviews). The research data were collected by using a questionnaire for achievement motivation and students’ satisfaction survey of the writing the scientific research proposal by inserting gamification on its steps, along with Interviews and product evaluation card, in order to answer research questions: 1) What is the impact of Gamification through the Learning Management System (Blackboard) towards stimulating achievement motivation to write the scientific research proposal among educational technology students at King Abdul Aziz University? and 2) To what extend are educational technology students satisfied with gamifying the scientific research proposal?. Research results came out with a good research proposal according to the standard of product evaluation card, the results showed increasing in students’ achievement motivation in writing research proposal at the beginning of the experiment, but it decreased with experiment passed time because of their study pressures. Their satisfaction was high about the experience and it’s enforced through Blackboard.